A synthetic HIV-1 Rev inhibitor interfering with the CRM1-mediated nuclear export - Daelemans, Dirk (National Academy of Sciences, 2002)
The HIV-1 Rev protein is an essential regulator of the HIV-1 mRNA expression that promotes the export of unspliced and partially spliced mRNA. The export receptor for the leucine-rich nuclear export signal (NES) of Rev has recently been recognized as CRM1. We identified a low molecular weight compound PKF050-638 as an inhibitor of HIV-1 Rev. This drug inhibits in a dose-dependent fashion Rev-dependent mRNA expression in a cellular assay for Rev function. We show that PKF050-638 is an inhibitor of the CRM1-mediated Rev nuclear export. By using a quantitative in vitro CRM1-NES cargo-binding assay, we could demonstrate that PKF050-638 disrupts CRM1-NES interaction. This mode of action is confirmed in cell culture because the drug reversibly interferes with the colocalization of CRM1 and Rev in the nucleolus of the cell. In addition, we prove that the inhibition is through direct interaction of the compound with Cys-539 of CRM1. These effects are similar to those of the known CRM1 inhibitor leptomycin B and suggest that the inhibitory effect of the compound is caused by binding to CRM1 at a similar site. The compound displayed strict structural requirements for its activity, as its enantiomer was inactive in all assays tested. These results show that we identified a drug that interferes with the CRM1-mediated nuclear export of Rev through inhibition of the CRM1-NES complex formation. The reversibility of its binding to CRM1 and its availability through chemical synthesis could make it useful for studying CRM1-mediated export pathways.